2016
DOI: 10.1080/03054985.2016.1215611
|View full text |Cite
|
Sign up to set email alerts
|

Does private schooling narrow wealth inequalities in learning outcomes? Evidence from East Africa

Abstract: In many low-and lower-middle-income countries, private schools are often considered to offer better quality of education than government schools. Yet, there is a lack of evidence to date on their role in reducing inequalities: namely, the extent to which private schooling improves learning among the most disadvantaged children. Our paper uses household survey data from Kenya, Tanzania, and Uganda to identify whether any observed impact of private schooling on core literacy and numeracy skills differs according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…In the absence of effective interventions focused on improving learning, such as PRIMR, there appear to be no additional impacts on learning if a child is sent to an LCPS, despite parental perceptions of higher quality in those schools (Zuilkowski et al, 2018). Our analytic approach, using residual student gains over time rather than cross-sectional scores, led us to overall findings that contrasted with much of the recent literature on LCPSs in Kenya, which has suggested that LCPSs are intrinsically higher-quality schools (Alcott & Rose, 2016;Ejakait et al, 2011) rather than schools that have higher outcomes because of selection bias. It also contrasts with the recent push in England to create a set of LCPSs (Tooley, 2018).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the absence of effective interventions focused on improving learning, such as PRIMR, there appear to be no additional impacts on learning if a child is sent to an LCPS, despite parental perceptions of higher quality in those schools (Zuilkowski et al, 2018). Our analytic approach, using residual student gains over time rather than cross-sectional scores, led us to overall findings that contrasted with much of the recent literature on LCPSs in Kenya, which has suggested that LCPSs are intrinsically higher-quality schools (Alcott & Rose, 2016;Ejakait et al, 2011) rather than schools that have higher outcomes because of selection bias. It also contrasts with the recent push in England to create a set of LCPSs (Tooley, 2018).…”
Section: Discussionmentioning
confidence: 81%
“…Although LCPSs may have lower student-teacher ratios and different disciplinary practices, their effects on academic performance are less clear. In their study of LCPSs and government schools in India, Ghana, Nigeria, and Kenya, found, on average, better student performance in LCPSs compared to government schools, a finding echoed by other studies conducted in Kenya (Alcott & Rose, 2016;Ejakait, Mutisya, Ezeh, Oketch, & Ngware, 2011;Ngware et al, 2013;Piper, King, & Mugenda, 2016;Piper & Mugenda, 2012). However, there is a lack of causal evidence of the effects of LCPS attendance on student performance.…”
Section: Background and Contextmentioning
confidence: 91%
“…Exemplifying the latter, a comparative study in the three East African countries, Tanzania, Kenya, and Uganda, indicates that although private schooling improves children's chances of learning the basics, it does not bridge the gap in learning inequalities between the wealthy and the underprivileged. The underprivileged are much less likely to be enrolled in private schools in each of the three countries (Alcott & Rose, 2016). Another study from Nepal highlights inequality, whereby middle-income households abandon public schools in favour of private ones (Bhatta, 2014).…”
Section: The Diversity Of Private Schools and Their Role In The Inequality Gapmentioning
confidence: 99%
“…However, an extensive review of the literature arrives at the conclusion that the evidence is ambiguous at best because of the inability to control for student background characteristics (Ashley et al, 2014). Controlling for student backgrounds is essential, since even among the poor it is typically the relatively more well-off who are able to afford to send their children to school in LFPSs (Alcott & Rose, 2016;Fennell & Malik, 2012;Harma, 2011;Languille, 2016;Singh & Bangay, 2014). The point here is that, despite the best efforts of researchers, it is very difficult to attain control and treatment samples that are comparable due to the fact that parents with relatively more resources, social capital, etc.…”
Section: Literature Reviewmentioning
confidence: 99%